Pathophysiology and treatment of iatrogenic abdominal hernia in feline - a Case report - de Faria, Barbra Gabriela Oliveira; Filho, Emanoel Ferreira Martins; Conceição, Deusdete Gomes; Neto, Francisco de Assis Dórea; Quessada, Ana Maria; Carneiro, Rosileide dos Santos; Neto, João Moreira da Costa (Brazilian Journal of Veterinary Medicine, 2016)
ABSTRACT. Faria B.G.O., Oriá A.P., Martins Filho E.F., Conceição D.G., Dórea Neto F.A., Quessada A.M., Carneiro R.S. & Costa Neto J.M. [Pathophysiology and treatment of iatrogenic abdominal hernia in feline - a Case report.] Fisiopatologia e tratamento de hérnia abdominal iatrogênica em felino - Relato de caso. Revista Brasileira de Medicina Veterinária, 38(Supl.1):26-32, 2016. Programa de Pós-Graduação Ciência Animal nos Trópicos, Universidade Federal da Bahia, Av. Ademar de Barros, 500, Ondina, Salvador, BA 40170-110, Brasil. E-mail: jmcn@ufba.br It describes the pathophysiology of iatrogenic latero dorsal abdominal hernia occurred in feline of two years and seven months old that has the muscle weakness of the right side of the abdominal wall like a predisposing factor, resulting from the deficient healing of a post-vaccination intramuscular abscess, occurred at four months of age. Subsequently, a chronic constipation picture, caused by fecal impaction was the triggering factor responsible for the increase of the internal abdominal pressure and subsequent formation of the hernia process. In reference to the surgical treatment, considering the tissue impairment of the abdominal muscles and tissue tension observed after its synthesis, we decided for the use of center equine phrenic preserved in glycerin to the appropriate strengthening of this structure. The analysis of the case highlights the value of management. The description of the pathophysiology, in addition to strengthen the concept of involvement in internal abdominal pressure in the genesis of abdominal hernias, clarifies the iatrogenic diagnosis of the hernia, in particular. In time, excels the effectiveness of the use of biological membrane, in this case, center equine phrenic preserved in glycerin, in the repair of abdominal wall.